2017
DOI: 10.1159/000480737
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy in Treating Lung Metastasis of Invasive Breast Cancer with Functional Vincristine Plus Dasatinib Liposomes

Abstract: Background: The metastasis of breast cancer is the leading cause of death, while lung metastasis is a major clinical phenomenon in patients with invasive breast cancer. The current treatment option comprising surgery, radiation, and standard chemotherapy cannot achieve a satisfactory effect on the treatment of lung metastasis of breast cancer. In this study, we report the potential of preventing lung metastasis of invasive breast cancer using the newly developed functional vincristine plus dasatinib liposomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Vincristine, a major compound of Catharanthus roseus , has been demonstrated to potently attenuate a series of malignancies, including colon cancer, metastatic breast cancer, and rhabdomyosarcoma [ 63 , 64 , 65 ]. The most therapeutic mechanism of inducing tumor death by vincristine is to break the polymerization of mitotic spindle microtubules and continuous arrests cell division during metaphase.…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%
“…Vincristine, a major compound of Catharanthus roseus , has been demonstrated to potently attenuate a series of malignancies, including colon cancer, metastatic breast cancer, and rhabdomyosarcoma [ 63 , 64 , 65 ]. The most therapeutic mechanism of inducing tumor death by vincristine is to break the polymerization of mitotic spindle microtubules and continuous arrests cell division during metaphase.…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%
“…At present, paclitaxel, vincristine and other spindle poisons are the first-line chemotherapy options for the majority of solid tumors, such as breast and ovarian cancer (17,18). These drugs affect the structure and function of spindles during the process of mitosis in tumor cells, destroying the kinetochore and affecting the adhesion of the tube and the integrity of the mitotic apparatus to prevent normal splitting of the chromosome centromere, which is originally placed in the center of the equatorial plate (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes have been widely used to combine anticancer drugs of different therapeutic classes [100]. Studies have shown that functional vincristine plus dasatinib liposomes can induce the cell cycle arrest at the G2/M phase, inducing apoptosis, inhibit adhesion, migration, and invasion of breast cancer cells [101]. The immune cycle checkpoint inhibitors namely programmed cell death protein-1 (PD-1) and its ligand PD-L1 interact to protect tissues from the host immune defense system.…”
Section: Liposomesmentioning
confidence: 99%